Efficient recovery of Fe (III) from dechroming sludge with a novel combined process of acidic leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Boxi Wu; Qingbiao Zhao; Kairui Zhou; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; Xiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Modeling of ammonia adsorption and desorption process based on lattice Boltzmann method for SCR applications - Bin Wang; Chenguang Hou; Xiangjin Kong; Boxi Shen; Guangdai Huang; Xuan Zhu; Jinou Song (Journal of Environmental Chemical Engineering, 2026)

Ochratoxin C induces zebrafish embryonic neurodevelopmental defects and cerebral hemorrhaging by downregulating Notch signaling - Boxi Hu; Dou Yang; Qiang Yuan; Zhipeng Wang; Jiejun Liu; Jiali Xu; Fasheng Liu; Shouhua Zhang; Xinjun Liao; Juhua Xiao; Zigang Cao (Journal of Environmental Sciences, 2026)

Efficient recovery of chromium from electroplating sludge by a two-step roasting process: Mechanisms and kinetics - Chengbin Zhong; Junxia Yu; Boxi Wu; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; YingYing Liu (Minerals Engineering, 2026)

Synergistic co-catalyst strategies for photo-thermal CO2 reduction into value-added fuels: A critical review on mechanisms, challenges, and future prospects - Maroof Ali Panhwar; Bachirou Guene Lougou; Muhammad Rafique; Wei Wang; Mustafa Azeem; Boxi Geng; Hao Zhang; Achraf Ghorbal; Yong Shuai (Fuel, 2025)

Functional characterization of transcription initiation factor TFIID subunit 7 in Penaeus vannamei (PvTAF7) and its interaction with YY1 in response to Vibrio challenge - Peikui Yang; Shuqin Wang; Tongying Chen; Qiongjun Zhao; Xuelian Ye; Boxi Zeng; Xianghui Zou; Yuzhong Zheng; Ruixuan Wang (Fish & Shellfish Immunology, 2025)

Synergistic Mn-doping and MXene coupling in sulfur-deficient In2S3 nanosheets for high-performance sodium-ion batteries - Manman Zhang; Qi An; Haocun Ba; Boxi Wang; Beibei Li; Chengjiang Deng; Liuyuan Ma; Yinghong Lan; Xiaoyan Han; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Oil Film Segmentation Method Using Marine Radar Based on Feature Fusion and Artificial Bee Colony Algorithm - Jin Xu; Bo Xu; Xiaoguang Mou; Boxi Yao; Zekun Guo; Xiang Wang; Yuanyuan Huang; Sihan Qian; Min Cheng; Peng Liu; Jianning Wu (Journal of Marine Science and Engineering, 2025)
In the wake of the continuous development of the international strategic petroleum reserve system, the tonnage and quantity of oil tankers have been increasing. This trend has driven the expansion of offshore oil exploration and transportation, resulting in frequent incidents of ship oil spills. Catastrophic impacts have been exerted on the marine environment by these accidents, posing a serious threat to economic development and ecological security. Therefore, there is an urgent need for efficient and reliable methods to detect oil spills in a timely manner and minimize potential losses as much as possible. In response to this challenge, a marine radar oil film segmentation method based on feature fusion and the artificial bee colony (ABC) algorithm is proposed in this study. Initially, the raw experimental data are preprocessed to obtain denoised radar images. Subsequently, grayscale adjustment and local contrast enhancement operations are carried out on the denoised images. Next, the gray level co-occurrence matrix (GLCM) features and Tamura features are extracted from the locally contrast-enhanced images. Then, the generalized least squares (GLS) method is employed to fuse the extracted texture features, yielding a new feature fusion map. Afterwards, the optimal processing threshold is determined to obtain effective wave regions by using the bimodal graph direct method. Finally, the ABC algorithm is utilized to segment the oil films. This method can provide data support for oil spill detection in marine radar images.

Photosynthetic physiology and stress-resistant biochemical properties reveal the invasive photo-adaptation strategy of marine green alga Codium fragile - Bingxin Huang; Boxi Li; Xulei Wang; Liming Rao; Jie Chen; Yang Dai; Lichun Wang; Zhiying Wang; Lanping Ding (Acta Oceanologica Sinica, 2025)

Rapid determination for tyrosine isomers in food based on N-acetyl-L-cysteine/Upconversion nanomaterials target-induced quench by chiral Electrochemiluminescence sensor - Zhe Wang; Yongjiao Ren; Boxi Zhou; Zhen Chen; Zixiao Wang; Junying Wang; Junping Wang (Food Chemistry, 2025)

Perfluorodecanoic acid induces the increase of innate cells in zebrafish embryos by upregulating oxidative stress levels - Juhua Xiao; Dou Yang; Boxi Hu; Wenwen Zha; Weirong Li; Ying Wang; Fasheng Liu; Xinjun Liao; Huimin Li; Qiang Tao; Shouhua Zhang; Zigang Cao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Unraveling dynamics and interactions of core microorganisms in the biodegradation of keratin-based feather wastes - Boxi Wang; Yuan Chen; Jin Chuan Wu; Qingxin Li (Journal of Environmental Management, 2024)

Individual differences determine the morphogenesis pattern and reproductive uniqueness of the invasive green macroalga, Chaetomorpha valida, with possible implications for its habitat adaptation - Bingxin Huang; Liming Rao; Yunyan Deng; Boxi Li; Zhiying Wang; Jie Chen; Lichun Wang; Yang Dai; Lanping Ding (Journal of Oceanology and Limnology, 2024)

Montmorillonite-coupled microbially induced carbonate precipitation (MICP) enhanced contaminant removal and carbon capture in cyanide tailings - Yaoting Duan; Lei Niu; Boxi Li; Yang He; Xin Xu; Caiqi Yu; Zhe Wang; Chunqiao Xiao; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2024)

Experimental and kinetic study on the solar-driven iron-based chemical looping dry reforming of methane - Hao Zhang; Dazhi Yang; Yong Shuai; Xiaomi Zhang; Boxi Geng; Boshu Jiang; Bachirou Guene Lougou; Dongmei Han; Qinghui Pan; Fuqiang Wang (Chemical Engineering Journal, 2024)

Fluorescent solid-state strips based on SiO2 shell-stabilized perovskite nanocrystals applying for magnetic aptasensing detection of aflatoxin B1 toxin in food - Mingfei Pan; Xiaochun Hu; Rui Gao; Boxi Zhou; Jingming Sun; Dan Zhang; Xuan Liu; Yixin Wang; Shuo Wang (Food Chemistry, 2024)

Long-term hourly air quality data bridging of neighboring sites using automated machine learning: A case study in the Greater Bay area of China - Boxi Wu; Cheng Wu; Yuchen Ye; Chenglei Pei; Tao Deng; Yong Jie Li; Xingcheng Lu; Lei Wang; Bin Hu; Mei Li; Dui Wu (Atmospheric Environment, 2024)

The role of strigolactone analog (GR24) in endogenous hormone metabolism and hormone-related gene expression in tobacco axillary buds - Huiyuan Tian; Boxi Tang; Wuwei Fan; Zhiyan Pan; Jiantao Peng; Yuanxiu Wang; Fan Liu; Guoqin Liu (Plant Cell Reports, 2024)

Safe reuse of wastewater: Effect of disinfection methods on microbial community - Boxi Wang; Robert Duran; Thierry Pigot; Cristiana Cravo-Laureau (Journal of Cleaner Production, 2023)